Peliosis Hepatis-The Chameleon: An Unusual Presentation Mimicking Liver Abscess - Ruchi Rastogi; Parveen Batra; Subhash Gupta; Anjali K. Gupta; Bharat Aggarwal; Shaleen Agarwal (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
Peliosis hepatis is a rare vascular condition characterized by multiple randomly distributed blood-filled cavities throughout the liver, ranging in size from a few millimeters to several centimeters in diameter. The appearance of peliotic lesion on imaging varies depending on morphologic type, concomitant hemorrhagic component, and presence or absence of background hepatic steatosis. Here, we report an unusual presentation of peliosis hepatis as an exophytic mass arising in liver parenchyma, mimicking a liver abscess.